Public ethics and local government in a context of economic crisis / Ética pública y gobierno local en un contexto de crisis económica - Bernabé Aldeguer Cerdá (Barataria, 2013)
The fall in public revenue by local governments, as a consequence of the finance dependence on the real estate sector, is combined with a process of fiscal adjustment and a growing demand for social services, which is result of rising socioeconomic exclusion rates (less consumption, business closures, and unemployment). The economic crisis, accompanied by a crisis of ethics and values, refers to the emergence of the Public Ethics as a tool for social policy-making and institutional strengthening. The incessant search for legitimacy and consensus, not so much in relation to the output of public social policies, but also about the dialog and deliberative process itself, puts local entities facing the challenges in the strengthening of the political body as a prerequisite for commissioning and developing successful participatory and deliberative processes. The promotion of socio-economic conditions to ensure social cohesion, freedom and equal opportunities, become a challenge that transcends the literalness and urgency of financial statements and budget processes in a fiscal adjustment context. The article reviews the main trends and challenges related to the role of Public Ethics in making public policy budget, citizen participation and social inclusion by local governments. All this, in a context of economic crisis, progressive social weakening, fiscal adjustment of the local public sector, public distrust for the institutions and growing axiological pluralism that is taken into account.